Gold(i) bridged dimeric and trimeric heterometallic Cr7Ni-based qubit systems and their characterization. Issue 12 (11th March 2021) - Asthana, Deepak; Lockyer, Selena J.; Nawaz, Selina; Woolfson, Robert J.; Timco, Grigore A.; Muryn, Christopher A.; Vitorica-Yrezabal, Iñigo J.; Collison, David; Burton, Neil A.; Winpenny, Richard E. P.
Abstract : Gold(i ) bridged dimeric and trimeric structures of a ground state spin S = 1/2 heterometallic Cr7 Ni wheel have been prepared and studied by continuous wave (CW) and pulsed wave EPR spectrometry. Abstract : Gold(i ) bridged dimeric and trimeric structures of a ground state spin S = 1/2 heterometallic Cr7 Ni wheel have been prepared and studied by continuous wave (CW) and pulsed wave EPR spectrometry. The Cr7 Ni relaxation time constants ( T 1 and T m ) show rates matching well with previous observations. Four pulse Double Electron Resonance (DEER) studies suggest presence of more than one conformations. Small Angle X-ray Scattering (SAXS) in conjunction with Molecular Dynamic (MD) Simulations were performed to look at the possible conformations in solution. In line with DEER results, simulation data further indicated more flexible molecular geometry in solution than the one in solid state.